Motivational duality and fake news reporting behavior: a polynomial regression with response surface analysis - Shen, Xiao-Liang; Liu, Lin-Yao; Li, Yang-Jun (Information Research an international electronic journal, 2025)
Context. Promoting social media users to report fake news is a crucial for curbing its spread, yet active reporters remain limited compared to those contributing to its proliferation. Purpose. This study examines how users' moral motivations affect their fake news reporting behavior. Specifically, it investigates how the dual dimensions of moral motivation (i.e., agency and communion), both in congruence or incongruence, affect reporting behavior. Method. Grounded in the reconciliation model of moral centrality, this study develops research hypotheses and tests them using over 13,000 reports and more than 4 million posts from 15,256 social media users. Empirical analysis employs dictionary-based text analysis method, and polynomial regression with response surface analysis. Findings. Users with congruent agency and communion motivations are more likely to report fake news, and this likelihood increases as the strength of these motivations grows. User heterogeneity analysis shows that unverified users report more when communion exceeds agency, while verified users report more when agency exceeds communion. Originality. This study presents a novel perspective on fake news reporting behavior by linking it to moral motivation and examining how the congruence or incongruence between agency and communion shapes reporting behavior, with distinct effects for verified and unverified social media users.